KANDUNGAN LOGAM BERAT PB, CU DAN ZN PADA SEDIMEN DAN TIRAM (Crassostrea cucullata Born) DI MUARA SUNGAI LOS KALA KECAMATAN MUARA SATU KOTA LHOKSEUMAWE PROVINSI ACEH - Irfan Emersida (LPPM Universitas Almuslim, 2021)
Analysis of heavy metals content Pb, Cu and Zn in sea water and Oyster (C. cucullata) in Los Kala River Estuary has been conducted from July – August 2014. Samples of sea water and Oyster (C. cucullata) were taken from five stations with three replicates at each station. Heavy metals content analysis was carried out at the Riau KLHK Laboratory with Atomic Abortion Spectrophotometer Shimadzu AA-7000. The results showed that average haeavy metals content in sediment were 14,668 µg/L (Pb), 20,293 µg/L (Cu) ), 68,669 µg/L (Zn) and in Oyster (C. cucullata) were 14,454 µg/g (Pb), 103,778 µg/g (Cu) ), 111,611 µg/g (Zn) respectively. Simple linear regression analysis indicates positive correlation between metals content in sediment and in Oyster (C. cucullata) with Y = 11,73 + 0,185X (r = 0,305) ; Y = 3,302 + 1,577X (r = 0,338) Zn and indicates negative correlation between metals content in sediment and in Oyster (C. cucullata) with Y = 93,76 +142,8X (r = 0,432) Zn.